1991
DOI: 10.1294/jes1990.2.21
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopathological Changes in Racehorses with Abrupt Deceleration of Speed during a Race

Abstract: Five racehorses were selected at the time of necropsy during a 4-year period involving about 500 thoroughbred horses. The 5 horses suddenly weakened during races and trailed in. Electrocardiographically, 3 of the 5 animals exhibited paroxysmal atrial fibrillation (AF) at rest, shortly after the races. Ten days to three months later, the 5 revealed exercise-induced ventricular premature contractions (VPCs) on the radiotelemetric electrocardiogram. Cardio pathologically focal lesions of myocardial fibrosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…On the other hand, no relation has been demonstrated between AF and SCD in the horse [10,29]. We have found that horses that have recovered from paroxysmal AF frequently reveal exercise-induced VPCs on the radiotelemetric ECG [22]. By contrast, apparently healthy horses without a history of AF have no arrhythmias during exercise [35].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…On the other hand, no relation has been demonstrated between AF and SCD in the horse [10,29]. We have found that horses that have recovered from paroxysmal AF frequently reveal exercise-induced VPCs on the radiotelemetric ECG [22]. By contrast, apparently healthy horses without a history of AF have no arrhythmias during exercise [35].…”
Section: Discussionmentioning
confidence: 87%
“…In particular, the occurrence of paroxysmal AF causes the horse to slow down during the race [2,22]. It is known that human AF can precipitate heart failure, angina and ventricular arrhythmia, and increases cardiovascular mortality and the rate of SCD [7,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the anatomical structure of the right atrium may be such that its upper portion of the anterolateral and medial regions would be most affected by this increased hemodynamic load and would develop most lesions. Interestingly, such location of myocardial fibrotic lesions in the right atrial wall has also been observed in racehorses with AF [1,19].…”
Section: Discussionmentioning
confidence: 90%